Takayasus arteritis a rare cause of hypertension and cardiac hypertrophy in Bangladeshi children- a case report and literature review - Taimur, Syed Dawood Md; Muinuddin, Md Golam; Jahan, Salma; Islam, Farzana; Ahmed, Tamzeed; Islam, Shiekh Md Shaheedul; Siddique, Md Abu; Huque, Syed Saimul (University Heart Journal, 2010)
Takayasu's arteritis or pulseless disease is a chornic large vessel vasculities the cause of which is largely unknown. Takayasu's arterities is seldom reported, because it is a rare disease affecting about only 3 (three) people of every million indivisuals throughout the world, most commonly among Asian female of childbearing age. It rarely causes happertension in children. We present an 11 years old girl without typical symptomatic manifestation and with a unique presentation of headache & swelling of the body for one year. She also complainted of examinational dyspnoea for same duration and abdominal pain for six months. Her clinical examination revealed very feeble left upper limb pulse with no radio-femoral delay, different blood pressure of both arms and limbs, systolic bruits audible in left 2nd intercostal space and grade-1 apical pansystolic murmur. Her coronary angiogram report showed diffuse narrowing of a long segment of abdominal aorta, severe stenosis of proximal left subclavian artery and stenosed right renal artery. In this article we will describe a Takayasu's arteritis (TA), a rare cause of childhood hypertension. Keywords: Takayasu's arteritis (TA);Vasculitis; Hypertension. DOI: 10.3329/uhj.v5i2.4565 University Heart Journal Vol.5(2) July 2009 pp.94-96